A DESINFORMAÇÃO NAS PLATAFORMAS DIGITAIS E A “POLÍTICA DE INFORMAÇÕES ENGANOSAS SOBRE A COVID-19” DO TWITTER: DESAFIOS E PERSPECTIVAS DA MODERAÇÃO DE CONTEÚDO - Crestani, Pillar Cornelli (2024)
This present article objetives to verify which are the strategies adopted by Twitter to oppose misinformation on its platform, in the context of the Covid-19 pandemic. From the formulation of this problem, expressed by the dedutive approach method, this research departed of a broad situation, demonstrated by the virtual disinformation phenomenon, especially in the Covid-19 pandemic, going to to verify a specific case, that is demonstrated by “Twitter’s Covid-19 Misleading Information Policy”. Allied to this methodological reference, the present study used the procedure monographic method, combining bibliographic and documentary research techniques, because was analyzed the “Twitter’s Covid-19 Misleading Information Policy”, on the Twitter website, and the studies of specialists in the field of Digital Law and technology. Based on the study, it was concluded that Twitter prohibits the posting of false content about Covid-19 that could harm people and, as a form of sanction for non-compliance with the guidelines, the platform establishes certain categories of intervention measures to be applied to posts that violate its policy, like: the exclusion of the tweet; marking offending content; and blocking or permanently suspending the user’s Twitter account.